1972
DOI: 10.1111/j.1432-1033.1972.tb19710.x
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Protein‐Containing Liposomes Injected into Rats

Abstract: [3H]Amyloglucosidase and 1311-labelled albumin were entrapped into liposomes (lipid spherules) composed of phosphatidyl choline, cholesterol and dicetyl phosphate (7 : 2 : 1 molar ratio). l3lI-labelled albumin was also entrapped in [3H]cholesterol-liposomes.Investigations on the fate in vivo following intravenous injection of such protein-containing liposomes into rats, showed that the bulk of liposomal radioactivity is removed from the blood within minutes. There is no measurable leakage of entrapped 1311-lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
1
6

Year Published

1975
1975
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(97 citation statements)
references
References 16 publications
4
86
1
6
Order By: Relevance
“…However, liposomes injected i.v. are mainly taken up by the cells of the liver and spleen (Gregoriadis & Ryman, 1972). Specific accumulation of liposomes in tumours, and particularly in tumour cells, would be of considerable advantage in improving the selectivity of anti-cancer drugs.…”
mentioning
confidence: 99%
“…However, liposomes injected i.v. are mainly taken up by the cells of the liver and spleen (Gregoriadis & Ryman, 1972). Specific accumulation of liposomes in tumours, and particularly in tumour cells, would be of considerable advantage in improving the selectivity of anti-cancer drugs.…”
mentioning
confidence: 99%
“…Unfortunately, when liposomes encounter the membranes of cells or organelles, they tend to resist uptake (6), provoke fusion with cell membranes (7,8), or remain adsorbed to cell surfaces where their contents remain unavailable to the cell interior (6). Although studies in vivo have shown uptake by rat liver and spleen of enzymes originally associated with injected liposomes (9,10), no compelling evidence has been presented that enzymes captured by liposomes can be endocytosed by lysosomes of undamaged cells in the absence of surface adsorption or direct fusion.…”
mentioning
confidence: 99%
“…When uptake was expressed as activity in whole organ, the liver became the most effective one (Fig. 1b), as observed by others (Gregoriadis and Ryman 1972). Relatively high et al…”
Section: Blood Content Of Brainmentioning
confidence: 49%